GOOD GOVERNANCE AND NATURAL RESOURCE CURSE; WHICH HYPOTHESIS IS PREVAILING IN ASEAN ECONOMIES? - Iskandar, Deden; Hendarto, Robertus Mulyo; Reza, Adhevyo (Economic Research Center, the Indonesian Institute of Sciences (P2E-LIPI), 2020)
This study aims to find the relevance of the natural resource curse and good governance hypothesis in ASEAN economies post-financial crises 1998. Employing Generalized Method of Moments (GMM), this study finds that good governance practices (Control of Corruption, Political Stability, and Voice and Accountability) play a role in the ASEAN economies after the great financial crisis. Thus, the hypothesis stating that good governance practices will improve economic development is confirmed. On the other hand, the observation of the natural resource curse hypothesis in ASEAN countries returns mixed results. The hypothesis states that natural resource abundance is associated with lower economic performance. This study finds that dependence on the natural resource by itself does not affect GDP. However, the natural resource curse occurs when countries with bad governance (low Control of Corruption) depend on agriculture resources. On the other hand, the natural resource becomes a blessing when the countries that rely on agriculture resources are supported with good governance practices in terms of strong Government Effectiveness, Political Stability, and Voice and Accountability.  Thus, the effect of natural resources on economic development depends on the quality of governance. This paper highlights the importance of observing the natural resource and good governance in interaction instead of in isolation and the relevance of disaggregating the indicators of good governance as well as natural resources.